A strategy for analyzing and enriching domain ontologies - Rico, Mariela (2010)
During the last years there is an increasing interest on the ontologies. The way in which the semantics of a domain entity is represented in an ontology may di er depending on the requirements that the ontology should satisfy. However, in general the richness is a desired quality attribute for an ontology. The contribution of this paper is a strategy for evaluating and enriching the representation of real entity semantics in a domain ontology. In addition, an application example is discussed.